2019
DOI: 10.1038/s41590-019-0330-4
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: γδ T cells producing interleukin-17A regulate adipose regulatory T cell homeostasis and thermogenesis

Abstract: In the version of this article initially published, a source of funding was not included in the Acknowledgements section. That section should include the following: P.J.M.O. was supported by EU FP7 PREPARE project 602525. The error has been corrected in the HTML and PDF version of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Secondly, we have not fully explored the link between immune cells, fat and heat regulation. For instance, recent studies have suggested that g/d T cells reside in fat tissues and regulate the response of mice to cold (144). We have noticed visible differences in the amount of visceral fat of mice housed in the 3 different conditions (SH, SI and SI+Nest; data not shown) but have not processed these tissues for detailed histological or cytofluorimetric analyses.…”
Section: Discussionmentioning
confidence: 78%
“…Secondly, we have not fully explored the link between immune cells, fat and heat regulation. For instance, recent studies have suggested that g/d T cells reside in fat tissues and regulate the response of mice to cold (144). We have noticed visible differences in the amount of visceral fat of mice housed in the 3 different conditions (SH, SI and SI+Nest; data not shown) but have not processed these tissues for detailed histological or cytofluorimetric analyses.…”
Section: Discussionmentioning
confidence: 78%